2010
DOI: 10.1177/001440291007600205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Curriculum Modifications on Access to the General Education Curriculum for Students with Disabilities

Abstract: r: This study investigated whether curriculum modifications predicted student and teacher behaviors related to the general education curriculum and if there were differences in ecolo^cal, student, and teacher variables depending on the presence of such curriculum modifications. The study observed 45 high school students with disabilities during instruction in core content areas. Findings indicated that there were significant differences in student and teacher variables depending on the presence of curriculum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 36 publications
7
74
0
5
Order By: Relevance
“…Shogren et al ( 2012 ) implemented a cluster randomized trial control group study to establish the effi cacy of the SDLMI on student academic and transition goal attainment and access to the general education curriculum for students with intellectual disability and learning disabilities. These fi ndings extended fi ndings from Lee, Wehmeyer, Soukup, and Palmer ( 2010 ), who in a smaller RCT also found that implementation of the SDLMI promoted student access to the general education curriculum.…”
Section: Self-determined Learning Model Of Instructionsupporting
confidence: 78%
“…Shogren et al ( 2012 ) implemented a cluster randomized trial control group study to establish the effi cacy of the SDLMI on student academic and transition goal attainment and access to the general education curriculum for students with intellectual disability and learning disabilities. These fi ndings extended fi ndings from Lee, Wehmeyer, Soukup, and Palmer ( 2010 ), who in a smaller RCT also found that implementation of the SDLMI promoted student access to the general education curriculum.…”
Section: Self-determined Learning Model Of Instructionsupporting
confidence: 78%
“…In addition, METs' adaptations were of lower quality and clarity than those of SETs and teaching assistants. In addition, Lee, Wehmeyer, Soukup, and Palmer (2010) found that students with disabilities increase their engagement in academic-related responses, while they decrease their competing behaviours, and that teachers perform fewer classroom management activities if curriculum modifications are used. Yet, many research studies in this area report lack of curriculum modifications in co-taught classes for students with disabilities (Antia, 1999;Buckley, 2005;Strogilos et al, 2015).…”
Section: Modifications Of the Curriculummentioning
confidence: 99%
“…Kern and her colleagues (2001) found that when teachers use curricular modifications, students' on-task behavior and work production improved. Similarly, Lee et al (2010) found that when curriculum modifications are used, students with special needs/ disabilities increased their engagement in academic-related responses and decreased their problematic behaviors. The authors also indicated that when curriculum modifications are used, teachers performed fewer classroom management activities.…”
Section: Research Findings On Differentiated Instructionmentioning
confidence: 93%
“…At the international level, even though the number of students with SEN in mainstream classrooms has increased, the type and the quality of education they receive remains a contentious issue (Morningstar, Shogren, Lee, & Born, 2015). Several authors have urged for the necessary modifications to increase the quality of education provided to students with SEN through differentiated instruction (King-Sears, 2008;Kurth & Keegan, 2014;Lee, Wehmeyer, Soukup, & Palmer, 2010).…”
Section: Research Findings On Differentiated Instructionmentioning
confidence: 99%